A diesel replacement strategy for off-grid systems based on progressive introduction of PV and batteries: An Indonesian case study. (1st November 2018) - Rodríguez-Gallegos, Carlos D.; Gandhi, Oktoviano; Bieri, Monika; Reindl, Thomas; Panda, S.K.
Highlights: Strategy to progressively optimize the sizing design of solar panels and batteries is proposed. No high initial investment is required. Bank loans and time-dependent parameters/prices are considered. Abstract: In many locations, grids are energized only by diesel generators (DG-only systems). Due to the requirements such as cost reduction and performance improvement, solar panels and batteries have increasingly been introduced into these grids. Nonetheless, many initiatives to hybridize the grids are still thwarted because of the high initial investment. In this work, a gradual diesel replacement strategy is proposed. The strategy starts with a lower initial investment and gradually adds solar panels and batteries in the subsequent years using accumulated savings from the lower diesel consumption. An Indonesian island is used as a case study to validate the proposed strategy. When only diesel generators are used, the life-cycle cost over a period of 25 years is 10.53 mil. USD. It is demonstrated through optimization that by lowering the initial investment to 0.25 mil. USD and gradually using the yearly savings to reinvest in purchasing additional solar panels and batteries, the life-cycle cost is reduced to 6.62 mil. USD (only 3.8% is required for the initial investment). Hence, with the proposed approach, the barrier of initial investment is minimized, and thus more renewable energy sources can be integrated into existing DG-only systems making the power generation more environment-friendly.